1999
DOI: 10.1177/105756779900900102
|View full text |Cite
|
Sign up to set email alerts
|

Victims' Needs and the Availability of Services: A Comparison of Burglary Victims in Poland, Hungary, and England

Abstract: Concern for victims of crime is reflected in a wide range of policy initiatives worldwide, but research on the needs of victims and the availability and appropriateness of victim services is largely restricted to a small number of Western industrial societies, and little of it is cross-national. This paper describes a comparative survey of burglary victims in five cities in Poland, Hungary, and England. Although the nature of household burglaries was found to vary in the three countries, victims' reactions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…If the impact of the loss was minor, the victim tended not to report due to ‘minor crime, minor loss, or loss of property having been recovered.’ In addition, as Mawby (1999) has found, adults with family dependants were more likely to report burglaries to the police because they had not only to consider their own safety, but also that of their children or spouse. Moreover, the fear of their families getting hurt was far more important than the property loss and themselves.…”
Section: Discussionmentioning
confidence: 96%
“…If the impact of the loss was minor, the victim tended not to report due to ‘minor crime, minor loss, or loss of property having been recovered.’ In addition, as Mawby (1999) has found, adults with family dependants were more likely to report burglaries to the police because they had not only to consider their own safety, but also that of their children or spouse. Moreover, the fear of their families getting hurt was far more important than the property loss and themselves.…”
Section: Discussionmentioning
confidence: 96%
“…First of all, information regarding security precautions such as closing windows and locking doors when leaving the house can be emphasized when the risk of burglary is likely to be elevated. Residents in neighbourhoods where a lot of burglaries occur can also be notified to keep an eye open and implement neighbourhood watch and asked to emphasize mutual caretaking (Mawby et al, 1999). The police, as a central actor, need to support residents and resident groups such as neighbourhood watch associations by means of information, advice and other forms of support.…”
Section: Discussionmentioning
confidence: 99%
“…Burglary has been described as a crime that has a powerful impact on its victims (Mawby et al, 1999). Burglary rates have declined slightly (Stepanek, 2011), but in Sweden the rate has remained relatively stable, with approximately 1 percent of surveyed households reporting a residential break-in per year according to the Swedish Crime Survey (BRÅ, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More dedicated cross-national research on victims' experiences of the police is perhaps best epitomised by Mawby et al's (Mawby, Brunt and Hambly, 1999;Mawby, Gorgenyi et al, 1999; see also Mawby, 1998) now dated comparison of victims in England, Germany, Hungary, Poland and the Czech Republic. They found marked cross-national differences, with victims in Poland the most dissatisfied, but suggested that in postcommunist societies victims' criticisms might be muted by perceptions that the police had been far worse under the old regime.…”
Section: Victims' Perceptions Of the Policementioning
confidence: 99%